Case Report: The Complexities of Managing Medications and the Importance of Deprescribing Anticholinergics in Older Adults - Elliott, Taylor; Eckmann, Lynne; Moga, Daniela C. (Frontiers in Pharmacology, 2021)
Potentially inappropriate anticholinergic medications (including over-the-counter products), polypharmacy, and the existence of communication barriers among members of the interprofessional team frequently contribute to clinical complexity in older adults. We present the case of a frail 86-year old female from the perspective of a community pharmacist managing outpatient medications and transitions of care. CD’s past medical history is significant for dementia, multiple falls, recurrent urinary tract infections, depression, cardiac arrhythmia, macular degeneration, chronic pain, depression, and cerebrovascular disease.